Efeito da entrevista motivacional no perfil de ambivalência e percepção de mudança na qualidade de vida relacionada à saúde bucal em pacientes com periodontite - Tatsch, Karen Finger (2024)
Periodontitis is a chronic inflammatory disease that leads to the progressive destruction of the tooth-supporting tissues, significantly impacting patients' quality of life. Effective dental biofilm control is essential for the prevention and treatment of this condition, but achieving lasting behavioral change in oral hygiene habits presents a major challenge. In this context, patient-centered counseling approaches, such as Motivational Interviewing (MI), have shown promise in promoting behavioral changes. The aim of this thesis was to evaluate whether conventional periodontal treatment (CPT), with or without the addition of MI, promotes a minimally important difference (MID) in the perception of improvement in oral health-related quality of life (OHRQoL) and whether this perception is associated with clinical and selfreported oral and general health outcomes in patients with periodontitis. Another objective was to identify whether patients with an ambivalent profile (characterized by conflicting feelings regarding behavioral change) and non-ambivalent patients showed clinical and self-perception differences in health and whether MI incorporated into CPT would provide additional benefits in oral hygiene behaviors. This study was conducted using secondary data from a randomized clinical trial, whose primary objective was to assess the impact of MI on improving oral hygiene behaviors in adults with periodontitis. Self-perception of improvement in OHRQoL was assessed using the MID, estimated as a 4.3-point difference in the Oral Health Impact Profile (OHIP-14) score. Individuals were categorized into two groups: MID ≥4.3 and MID <4.3. Patients were classified as ambivalent or non-ambivalent both by the importance ruler (<8 and ≥8, respectively) and by their discourse during MI sessions, categorized as “Ambivalent Talk” or “Change Talk.” Clinical variables—Gingival Index (GI), Plaque Index (PII), and Bleeding on Probing (BoP)—were evaluated at four time points (baseline, 15, 30, and 60 days), and differences in mean values of these indicators were analyzed using mixed linear models. The Mann-Whitney and Chi-square tests were used to compare continuous and categorical variables between groups. The results indicated that patients who perceived a minimally important improvement in OHRQoL (MID ≥4.3) had worse self-perception of oral and general health at baseline, as well as greater variations in clinical variables over time. For these patients, the addition of MI increased self-awareness regarding oral health, even though it did not lead to better clinical outcomes compared to the MID <4.3 group. Ambivalent patients (ruler <8) exhibited lower self-confidence in changing hygiene habits, resulting in lower treatment adherence. However, those who demonstrated “Ambivalent Talk” and received more MI sessions achieved better clinical outcomes. We conclude that personalized approaches, such as MI, are essential in the treatment of periodontitis, as they contribute to clinical improvement and enhance quality of life perception, especially in ambivalent patients regarding behavior change.